2020
DOI: 10.1177/0954406220970590
|View full text |Cite
|
Sign up to set email alerts
|

Surface texture improvement of magnetic and non magnetic materials using magnetic abrasive finishing process

Abstract: The present study focused on surface texture characteristics of magnetic material, Mild steel (MS) as well as nonmagnetic material, Aluminum 2024 (Al 2024) alloy with the application of a laboratory-developed magnetic abrasive finishing (MAF) process. MAF is one of the unconventional finishing processes to attain a satisfactory finishing level up to nanoscale. In MAF, the surface finish is controlled by a flexible magnetic abrasive brush (FMAB) which has a combination of abrasives (Al2O3, SiC, etc.) and magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Studies of abrasive finishing of aluminium and its alloys in a magnetic field have received considerable attention in literature (23,24). For example, in the work of Khomich (23) the influence of technological tool on the number of inclusions, micro-sharpening and removal of oxide film from the flanks of sheets from aluminium alloy of Al-Mg system (grades 1560 (AMg-6)) was studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of abrasive finishing of aluminium and its alloys in a magnetic field have received considerable attention in literature (23,24). For example, in the work of Khomich (23) the influence of technological tool on the number of inclusions, micro-sharpening and removal of oxide film from the flanks of sheets from aluminium alloy of Al-Mg system (grades 1560 (AMg-6)) was studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that rational selection of mode parameters and type of technological tool allows to perform defect-free abrasive finishing of sheet edges in a magnetic field. The criteria of surface roughness and its morphology after abrasive finishing in a magnetic field of surfaces of parts made of aluminium alloy of Al-Cu-Mg system (grades 2024 (D16)) has been analyzed in the work of Anjaneuli and Venkatesh (24). It was revealed that the following factors have the main influence on the quality of parts surfaces: stress, allowing to change the stiffness of the technological tool; feed rate, providing the process of micro-cutting.…”
Section: Introductionmentioning
confidence: 99%
“…32 To overcome these challenges, Venkatesh et al 33 studied the surface integrity of Al2024 using the ultrasonic-assisted abrasive flow machining (UAAFM) process, and the authors found that the percentage change in surface roughness of Al2024 was improved by 85.12%. In another attempt, Anjaneyulu and Venkatesh 34 proposed magnetic abrasive finishing (MAF) process to improve the surface texture of Al2024, and they reported that the surface texture of Al2024 was improved by 65%.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several established finishing processes use MR-fluid as a polishing medium, including magneto-rheological finishing (MRF), magneto-rheological abrasive flow finishing (MRAFF), rotational magneto-rheological finishing (R-MRAFF) and ball end magnetorheological finishing (BEMRF). [2][3][4] Ferromagnetic particles, abrasive, carrier mediums and essential additives are primary constituents of these fluids. 5 The action of ferromagnetic and abrasive particles as they form a soft magnetic abrasive brush will have a significant impact on the performance of the MR-fluid.…”
Section: Introductionmentioning
confidence: 99%